Identifikasi, Frekwensi dan Intensitas Serangan Hama Penyakit pada Shorea balangeran (Korth.) Burck pada Persemaian BPDASHL Kahayan, Tumbang Nusa, Kalimantan Tengah (Identification, Frequency and Intensity of Pets Attacks on Shorea balangeran (Korth.) Bur - Saragi, Suryati Marito; Firdara, Eritha K; Putir, Patricia E (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2019)
Shorea balangeran is native species of peat swamp forests that have a relatively faster growth than other tress in the same place. This species is in the category of critically endangered (CR). The purpose of this research is to identify the damage level of Shorea balangeran that be caused by pests and diseases. The research was conducted in Nurseryof Watershed Management Agency and Protection Forest of Kahayan. Research method used simple random sampling with amount of samples were 800 Shorea balangeran. The research were conducted start from May to December, 2016. The results of research show the some pests and diseases that attack Shorea balangeran, they ar grasshopper, caterpillars fire, leaf spot disease, sooty mold, leaf rust, and leaf galls. They are sequentially caused by Catantops splendens, Thosea sp., Pestalotia sp., Capnodium sp., Hemileia sp., and the pests from Order Hymenoptera. The intensity of pest attack in Shorea balangeran is 5.88% and a frequency 1.5%. The intensity of disease is 19.1% and a frequency 58.5%. Both combination are 7.13% and 2.65%.